Dependence of Pulsation Mode of Cepheids on Metallicity - Zhang, Zehao; Jiang, Biwei; Ren, Yi; Chen, Xiaodian; Wang, Shu (The Astrophysical journal, 2022)
The Cepheid variables in the Small Magellanic Cloud (SMC), the Large Magellanic Cloud (LMC), the Milky Way, M33, and M31 are used to examine the dependence of pulsation mode on metallicity, which was previously found in red supergiants. The initial samples of Cepheids are collected from the Cepheid catalogs identified from the Optical Gravitational Lensing Experiment, PS1, DIRECT, Wide-field Infrared Survey Explorer, and Zwicky Transient Facility surveys. The contaminants are removed with the help of the Gaia/EDR3 astrometric information for extra galaxies or by comparing the geometric distance and the distance from the P – L relation for the Milky Way. The division of fundamental (FU) and first-overtone (1O) modes is refined according to the gap between the two modes in the P – L diagram of the objects in each galaxy. The ratio of FU/(FU+1O) is found to be 0.59, 0.60, 0.69, 0.83, and 0.85 for the SMC, the LMC, the Milky Way, M33, and M31, respectively, in order of metallicity, which confirms that the pulsation mode depends on metallicity in the way that the ratio of FU/(FU+1O) increases with metallicity. This dependence is not changed if the incompleteness of the samples is taken into account.